ANALISIS PERILAKU NASABAH NONMUSLIM MEMILIH SIMPANAN DI PERBANKAN SYARIAH - Aqdhiat Pradipta (CALYPTRA, 2017)
ABSTRACT The purpose of this study is to determine the development of non-Muslim customers of Islamic banking in Surabaya. To determine the result, a research of the customer behavior of non-Muslims in Islamic banking in choosing a savings product mudaraba has been done. This study uses primary data collection. The primary data was obtained through direct interviews of the non-Muslim customers in the area of Surabaya. Some factors that affect the customers’ interest are non-Muslim customers' mindset of the Islamic bank, the knowledge of the usury prohibition, and the benefits that non-Muslim customer will get in Islamic banks. This study used a qualitative approach and triangulation data method. The results of the analysis of the six respondents indicated that there is a dominating influence on the behavior of non-Muslim customers in choosing a mudaraba savings product in Islamic banking. This study was intended to raise the customers’ interests of Islamic banks’ products, so the Islamic banks can compete with the conventional banks in the future. Keywords: development of non-Muslim customers, products mudaraba Islamic Bank.